MEMBANGUN GENERASI CERDAS FINANSIAL DI ERA DIGITAL: LITERASI KEUANGAN PADA SISWA MA DARUL HUDA DESA BAWAHAN PASAR KECAMATAN MATRAMAN KABUPATEN BANJAR - Karimah, Husna; Malihah, Lola; Anwar, Mukhlis Kaspul; Hidayatullah, Muhammad Syarif; Afif, Ahmad Musfida (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
The rapid development of digital technology in Indonesia has transformed various sectors, including the financial sector. As the country transitions toward a cashless society, it is crucial to strengthen financial literacy, especially among adolescents. This community service activity aimed to increase the understanding and awareness of digital financial literacy among students of MA Darul Huda through a participatory educational program. The method involved structured stages, including preparation, material presentation, digital wallet usage simulation, and interactive discussion. The results showed high enthusiasm from participants, who actively engaged in discussions and demonstrated improved understanding of digital financial services and potential risks. Although no pre- or post-test was conducted, qualitative evaluation revealed a positive impact through verbal feedback, teacher responses, and student involvement. This program is expected to contribute to building a generation that is financially responsible and aware of digital transaction risks, particularly within Islamic educational environments.